(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The production of raw cement results in carbon emissions into the environment which is a serious agenda that needs to be solved quickly before it’s too late for the environment. Almost 8% of total carbon emissions from all over the world come from the cement industry. Billions of tons of carbon dioxide gas are being released into the environment when cement is produced in the manufacturing plants which are damaging the ozone layer of the earth. An alternative solution to the problem may be the use of sustainable concrete prepared by replacing some portion of cement with agro-industrial waste materials such as rice straw ash, foundry sand, rice husk ash etc. In the present study, use of rice straw ash and foundry sand as partial replacement of cement and fine aggregate has been investigated. The sustainable concrete of M35 grade using rice straw ash (5%, 10%, 15% and 20%) and foundry sand (5%, 10%, 15% and 20%) by partial replacement of cement has been prepared and various properties of concrete have been investigated.